Proton Pump Inhibitors and the Risk of Community-Acquired Pneumonia: An Updated Meta-analysis. Issue 5 (May 2022) - Xun, Xuejiao; Yin, Qifan; Fu, Yuhao; He, Xueru; Dong, Zhanjun
Background: Some studies suggested an increased risk of community-acquired pneumonia (CAP) among proton pump inhibitors (PPI) users. However, the published evidence is inadequate to define the association between PPI use and the risk of CAP. Objective: The aims of our meta-analysis were to systematically assess the association between the risk of CAP and PPI use in adults to reduce the adverse effects of PPI and ensure the safety of medication for patients. Methods: A comprehensive literature search was conducted, published between January 1, 2004, and February 1, 2021. The primary outcome was the incidence of CAP. This meta-analysis was performed using odds ratios (ORs) with 95% CIs as effective measures; 13 studies including 2 098 804 patients were enrolled in our meta-analysis. Results: Our study revealed that the incidence of CAP was higher in PPI users than non -PPI users [OR = 1.37 (95% CI = 1.22–1.53)], especially for PPI duration < 30 days [OR = 1.49 (95% CI = 1.34–1.66)]. Compared with non-PPI use, PPI use increased the incidence of CAP in the stroke disease population [OR = 1.52 (95% CI = 1.33–1.75)], but not in the liver disease population [OR = 1.13 (95% CI = 0.98–1.30)]. Conclusions and Relevance: Using PPI could increase the risk of CAP when compared to not using PPI. PPI use increased the incidence of CAP in patients with stroke. Clinicians and clinical pharmacists should weigh the benefits before medication and strictly control the indication of the prescription, so as to reduce adverse reactions.